DEVELOPMENT OF HISTORICAL CALENDER MEDIA (KARAH) TO IMPROVE HISTORY LEARNING MOTIVATION OF STUDENTS IN CLASS XI OF STATE VOCATIONAL HIGH SCHOOL 2 PEKANBARU: Pengembangan Media Kalender Sejarah (KARAH) Untuk Peningkatan Motivasi Belajar Sejarah Peserta Didik Kelas XI SMK Negeri 2 Pekanbaru - Tiara Putri Afriani; Ahmal; Yuliantoro (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to develop learning media based on historical calendars to determine the feasibility of learning media based on historical calendars obtained from the perceptions of Class XI students of SMK Negeri 2 Pekanbaru, to determine the increase in historical motivation of Class XI students of SMK Negeri 2 Pekanbaru by using historical calendar learning media. The method used in this study is the Research and Development method with the ADDIE model. The validation results by media experts obtained 90% with a very feasible category, material experts obtained 82% with a very feasible category. From the results of the student motivation questionnaire after using the historical calendar media, 83.94% were obtained in the very feasible category and a positive response to the historical calendar learning media by obtaining 96% with a very feasible category. It can be concluded that the historical calendar media learning media can increase the motivation to learn history of class XI students of SMK Negeri 2 Pekanbaru.